Intramedular Malignant Peripheral Nerve Sheath Tumor at C3 Level in a Dog - Cavalcanti, Ellen Bethania de Oliveira; Zoppi Salvador, Ariela; Frasson Vieira, Luisa; Pereira de Oliveira, Mateus; Silva Veroneze, Ágatha; Signorelli Maciel, Natália; Cancian Baiotto, Gustavo; Marcolongo Pereira, Clairton (Acta Scientiae Veterinariae, 2024)
Background: Malignant peripheral nerve sheath tumors (MPNSTs) are rare sarcomas in domestic animals, originating from peripheral neural cells or cells associated with the peripheral nerve sheath. These tumors primarily occur in the peripheral nerves of the brachial plexus and may occasionally invade the spinal cord. Diagnosing MPNSTs is challenging owing to the primary clinical sign being progressive claudication, which can be of neurogenic or musculoskeletal origin. Thus, this study aimed to report a case of MPNST located at the C3 level in the vertebral canal, focusing on the clinical, imaging, and surgical aspects of the case. Case: A 9-year-old male mongrel dog, suffering from upper motor neuron tetraparesis, was treated for ataxia and nail dragging on the thoracic limbs. These symptoms later progressed to the pelvic limbs and eventually led to lateral decubitus. Myelotomography revealed a 2 cm neoplasm in the vertebral canal, compressing the spinal cord between the C2-C3 vertebral processes. The patient underwent decompressive surgery via a left dorsal approach to the vertebrae. A hemilaminectomy was performed between C2-C3, removing the laminar bone and exposing the spinal cord and nerve root of the segment. The mass, located in the nerve root region, was carefully separated from adjacent tissues, and removed. The tumor’s histology was consistent with MPNSTs. The patient’s neurological condition, which had been rapidly deteriorating, improved following spinal cord decompression surgery and mass extirpation. After a 3-day hospital stay, the patient was discharged for homecare. Five days post-surgery, the animal exhibited a return of neurological and ambulatory functions. The surgical procedure was the sole treatment method employed against this sarcoma. However, tumor recurrence was observed 270 days post-resection of the mass in the medullary canal. Given the unfavorable prognosis, the animal was euthanized. Discussion: Spinal cord tumors are categorized based on their location and segmentation relative to the spinal cord and dura mater. These categories include intramedullary, intradural-extramedullary, and extradural-extramedullary. Imaging tests such as magnetic resonance imaging (MRI) and computed tomography are more effective in locating and classifying spinal cord tumors than X-rays. Historically, myelography has been utilized to outline the subarachnoid space and ascertain the presence of spinal cord compression or expansion. However, MRI provides superior visualization. In this instance, tomography was employed to both verify the neoplasm compressing the spinal cord and to aid in surgical planning. Misdiagnosis of this condition as musculoskeletal claudication is common, leading to a delayed diagnosis of MPNSTs and an unfavorable prognosis. Hematological and biochemical tests are recommended for a general patient evaluation, but primary alterations in these tests are typically not present in patients with MPNSTs. Regarding treatment, total surgical resection of the neoplasm is most advised, as this malignant neoplasm is generally resistant to chemotherapy and radiotherapy. Given the rarity and progression of this disease, it is increasingly important to recognize the clinical signs specific to the case described, in order to establish the correct diagnostic methods and treatment protocols for each patient. Therefore, early diagnosis, grounded in a thorough clinical examination and supplemented by imaging tests, should be paired with aggressive surgical intervention. This approach aims to enhance the prognosis, quality of life, and survival rate of these patients. Keywords: dog, neoplasm, sarcoma, neurology.